Water-resistant free-standing DNA-complexed films with antioxidant and H2O2-responsive activity. Issue 15 (29th March 2023) - Lee, Jayeon; Tandon, Anshula; Mariyappan, Karthikeyan; Kokkiligadda, Samanth; Jeon, Sohee; Jeong, Jun-Ho; Park, Sung Ha
Abstract : Water-insoluble DNA complexes are suitable for producing free-standing DNA films due to their low water sensitivity, which prevents their rapid degradation in aqueous environments. Abstract : Water-insoluble DNA complexes are suitable for producing free-standing DNA films due to their low water sensitivity, which prevents their rapid degradation in aqueous environments. Here, we proposed two types of free-standing films that exhibit low dissolution rates in water: low molecular weight chitosan (LCS)–DNA films and phosphatidylcholine (PC)–cetyltrimethylammonium (CTMA)–DNA films. The structure and binding characteristics of the LCS–DNA and PC–CTMA–DNA complexes were investigated with UV-Vis spectroscopy and via the fluorescent characteristics of daunorubicin bound to them. A simple drop-casting method was then adopted for both complexes to fabricate free-standing films. An increase in antioxidant activity and water-resistance of the LCS–DNA DNA film was observed when the molar ratio of LCS to DNA was increased, but the dissolution rate of the LCS–DNA film was also dependent on the ionic strength of the dissolving solution. Fourteen days were required to dissolve the LCS–DNA film in deionized water, whereas immediate dissolution was observed in 1× phosphate-buffered saline (PBS). Deformation of the PC–CTMA–DNA film was accelerated by H2 O2, such that the PC–CTMA–DNA film was degraded after 21 days of immersion in 1× PBS with H2 O2 . Due to the low dissolution rate in water and antioxidant activity, the free-standing LCS–DNA film should be able to store and protect embedded clinical materials, such as proteins and intercalating drugs, from moisture and enable localized delivery of treatments to designated sites. Also, the free-standing PC–CTMA–DNA film could be a biocompatible candidate for use as a membrane or sensor for detecting the levels of reactive oxygen species.